2020
DOI: 10.1038/s41598-019-57105-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of STarT Back Tool and the short form of the Örebro Musculoskeletal Pain Screening Questionnaire with multidimensional risk factors

Abstract: the Short form of the Örebro Musculoskeletal pain Screening Questionnaire (ÖMpSQ-short) and the Start Back tool (SBt) have been developed to screen for risk factors for future low back pain (LBp)related disability and work loss respectively. The aim of this study was to investigate the accordance of the two questionnaires and to evaluate the accumulation of risk factors in the risk groups of both screening tools in a large population-based sample. The study population consisted of 3079 participants of the Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
21
0
4
Order By: Relevance
“…Advice, reassurance, encouragement of physical activity, and psychotherapy have gradually become recommended as first‐line care for LBP patients 49,50 . Among all above nondrug treatment measures, relief of anxiety to alleviate LBP has recently received progressive attention 51,52 . Although there may be some controversy, recent studies indicate that SIRT1 plays important roles in the pathophysiology and treatment of anxiety 53‐55 .…”
Section: Discussionmentioning
confidence: 99%
“…Advice, reassurance, encouragement of physical activity, and psychotherapy have gradually become recommended as first‐line care for LBP patients 49,50 . Among all above nondrug treatment measures, relief of anxiety to alleviate LBP has recently received progressive attention 51,52 . Although there may be some controversy, recent studies indicate that SIRT1 plays important roles in the pathophysiology and treatment of anxiety 53‐55 .…”
Section: Discussionmentioning
confidence: 99%
“…We will encourage the HCPs to classify the patients into low‐, moderate‐, or high‐risk groups during the first OHS visit, based on the SBT 20 . The occupational health physicians will initially plan the individual treatment process.…”
Section: Interventionmentioning
confidence: 99%
“…We will also deliver a written educational package to support the HCPs who received training, to enable them to share their ideas on the BPS approach and the use of the We will encourage the HCPs to classify the patients into low-, moderate-, or high-risk groups during the first OHS visit, based on the SBT. 20 The occupational health physicians will initially plan the individual treatment process. Medium-risk patients will receive similar treatment to those in the low-risk group.…”
Section: Patient Recruitment and Eligibility Criteriamentioning
confidence: 99%
“…to group patients into three categories of risk of poor outcome (persistent disabling symptoms)low, medium and high risk. It comprises modifiable factors (i. e. biomedical, psychological and social) for LBP disability [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that SBT is a tool that can be used to predict future disability among individuals with LBP [6,8,16]. Also, studies have reported varying degrees of associations between SBT, disability and some psychosocial variables [15,17]. Further, the convergent validity, which refers to the degree to which two measures capture a common construct [18] (in this case the SBT and other full-length modifiable risk factors such as the pain catastrophizing, fear-avoidance beliefs and kinesiophobia), has not been fully investigated for the SBT.…”
Section: Introductionmentioning
confidence: 99%